3D Graphene Foam Reinforced Low‐Temperature Ceramic with Multifunctional Mechanical, Electrical, and Thermal Properties. Issue 7 (2nd April 2019) - Thomas, Tony; Zhang, Cheng; Nautiyal, Pranjal; Boesl, Benjamin; Agarwal, Arvind
Abstract : Graphene foam reinforced multifunctional ceramic composite is fabricated in this study. Graphene foam has a 3D macroporous architecture, which is filled with a low temperature co‐fired (LTCC) ceramic phase. The composite microstructure is engineered by three‐step fabrication scheme: infiltration of porous graphene foam with ceramic slurry, solidification to form a green body, and finally, pressure and temperature‐assisted sintering to produce a dense composite with intimate ceramic/graphene interface. Graphene foam is found to retain its 3D structure. The interconnected network of nodes and branches induces superior fracture toughness, load‐bearing capacity, and thermal − electrical transport characteristics. Addition of mere 0.18 wt% graphene foam results in a 480% improvement in the fracture energy. Sub‐surface examination reveals extensive crack deflection due to graphene foam's cellular units, highlighting the advantage of a 3D filler. Graphene foam also induces an impressive electrical conductivity of 165 S m −1 in an otherwise insulator ceramic. In situ infrared thermal imaging demonstrates enhanced thermal transportability in ceramic due to graphene foam. These findings attest the significance of 3D graphene foam to develop multifunctional ceramic composites in load‐bearing structures, thermal management, and electro‐mechanical devices. The synthesis scheme presented here is promising for facile and scalable manufacturing of this new class of materials. Abstract : Dense ceramic reinforced with 3D Graphene Foam with superior mechanical and thermo‐ electrical properties make up for a new class of advanced engineering composites for applications like advanced sensors, bio‐implants, MEMS/NEMS, and electronic devices. The proposed three steps fabrication process can assist in the development of dense engineering materials reinforced with light weight, porous reticulated foam structure thus enabling material system with superior properties otherwise which are limited to infiltrating low viscosity polymers.